Induksi Poliploidi pada Tanaman Talas (Colocasia esculenta (L.) Schott) Kultivar Kaliurang dengan Perlakuan Kolkisin secara In Vitro - Ermayanti, Tri Muji; Wijayanta, Ardian Nur; Ratnadewi, Diah (Perhimpunan Biologi Indonesia, 2018)
ABSTRACTGenetic modification to increase productivity and other better growth characteristics of Kaliurang taro could be done by various methods; one of them is polyploid induction. Kaliurang taro has performed excellent traits, it is resistant to leaf blight disease and pests. Polyploid plants of Kaliurang taro are expected to have excellent char-acteristics and increased productivity. The objective to this study was to obtain an efficient method through in vitro induction of polyploidy using colchicine on Kaliurang taro. Aseptic plantlets of Kaliurang taro were soaked in colchicine solution at 0.05, 0.1 and 0.2% for 1, 2 and 3 days. Control was untreated plantlets. Each treatment consisted of 12 replicates. The colchicine-treated plantlets were then planted on MS medium containing 2 mg/L BAP, 1 mg/L thiamine and 2 mg/L adenine. Survival rate and vegetative growth of plantlets were observed every week for 8 weeks after planting. The results showed that increasing colchicine concentra-tion and the soaking period produced planlets with various survival rate. Flowcytometric analysis indicated that the treatment of soaking the plantlets in 0.05% colchicine for 1 day resulted in 14.3% of tetraploid plantlets. The most efficient of colchicine treatment was 0.2% for 3 days, resulting in 57.1% tetraploids, with the efficient value of 33.3%. There was chromosome multiplication from diploid to tetraploid which was confirmed through both flowcytometric analysis and chromosomes counting.Keywords: Taro (Colocasia esculenta L.), Kaliurang, in vitro, flowcytometer, chromosome multiplication, tetraploids